War brought home: Post-traumatic stress disorder in the post-Vietnam America through the documentary form of Emily Mann‘s play still life - Radovanović Aleksandar (Temida)
The collective moral dilemma that the United States society plunged into during the Vietnam War was intensified by the problem of Post-Traumatic Stress Disorder, which assumed undreamed- of proportions among returnees from the front. In her play Still Life, Emily Mann uses the example of a war veteran in order to examine PTSD not only in the context of war brutality which scars the warrior’s psyche, but also in the light of malign social circumstances which contribute to the development of the illness. The play suggests that the spread of PTSD was rooted not only in the technological advancement which enhanced the destructive potential of weaponry, but also in the state ideology which manifested itself in dehumanization of the enemy, shifting the burning issue of racism to the frontline, and enlistment policy based on class and racial discrimination. Traumatic experiences of the play‘s protagonists create an image of America in which boot camp for Vietnam was not limited to Parris Island, but pervaded the society through family and institutional dysfunction. Their confessions trace the war on its way back home, as a place from which it has sprung and is still being waged in, finding its victims both in veterans and people in their immediate surroundings. The playwright employs “Theatre of Testimony” in order to dramatize and simultaneously document her findings, which is why this paper deals in equal measure with her dramatic method and the way the content of the play interacts with the Vietnam heritage.